2015
DOI: 10.1177/0394632015572751
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm activity of pseudoalteromonas haloplanktis tac125 against staphylococcus epidermidis biofilm: Evidence of a signal molecule involvement?

Abstract: Staphylococcus epidermidis is recognized as cause of biofilm-associated infections and interest in the development of new approaches for S. epidermidis biofilm treatment has increased. In a previous paper we reported that the supernatant of Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 presents an anti-biofilm activity against S. epidermidis and preliminary physico-chemical characterization of the supernatant suggested that this activity is due to a polysaccharide. In this work we further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…The results in Figure 4 show that the supernatant was significantly more effective than cells against diatom biofilm formation, and that the competition for nutrients did not significantly contribute to the inhibition effect of the tested strain against biofilm formation of Stauroneis sp. Our results were similar to many reports of the cell-free supernatant, such as the supernatant of Pseudomonas fluorescens containing the quorum sensing signal affecting the growth, biofilm development, and spoilage potential of Shewanella baltica [ 42 ], the cell-free supernatant of a marine bacterium Pseudoalteromonas haloplanktis containing a signal molecule that identifies as a long-chain fatty acid active against Staphylococcus epidermidis [ 43 , 44 ], and the spent medium of a coisolated bacteria inducing diatom Achnanthidium minutissimum capsule and biofilm formation [ 10 ]. Therefore, we propose that metabolites of the tested strain in the supernatant are responsible for the activity.…”
Section: Discussionsupporting
confidence: 90%
“…The results in Figure 4 show that the supernatant was significantly more effective than cells against diatom biofilm formation, and that the competition for nutrients did not significantly contribute to the inhibition effect of the tested strain against biofilm formation of Stauroneis sp. Our results were similar to many reports of the cell-free supernatant, such as the supernatant of Pseudomonas fluorescens containing the quorum sensing signal affecting the growth, biofilm development, and spoilage potential of Shewanella baltica [ 42 ], the cell-free supernatant of a marine bacterium Pseudoalteromonas haloplanktis containing a signal molecule that identifies as a long-chain fatty acid active against Staphylococcus epidermidis [ 43 , 44 ], and the spent medium of a coisolated bacteria inducing diatom Achnanthidium minutissimum capsule and biofilm formation [ 10 ]. Therefore, we propose that metabolites of the tested strain in the supernatant are responsible for the activity.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, we observed that Antarctic marine bacterium Pseudoalteromonas haloplanktis TAC125 produces and secretes several compounds of biotechnological interest ( Papaleo et al, 2013 ), including molecules inhibiting the biofilm of the human pathogen S. epidermidis ( Papa et al, 2013b ; Parrilli et al, 2015 ). This activity impairs biofilm development and disaggregates the mature biofilm without affecting bacterial viability, showing that its action is specifically directed against biofilm ( Papa et al, 2013b ; Parrilli et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The search for QSI compounds has since turned to the ocean and its abundant variety of organisms, many of which are already known to produce useful bioactive compounds, such as halogenated furanones produced by the red alga D. pulchra (Rasmussen et al ., 2000), brominated alkaloids from Flustra foliacea (Peters et al ., 2003), and kojic acid from E. knighti (Dobretsov et al ., 2011). More recently, the culture supernatant from Antarctic marine bacterium P. haloplanktis TAC125 was shown to impair the formation of S. epidermidis biofilm (Papa et al ., 2013; Parrilli et al ., 2015). These findings demonstrate that QSI compounds are valuable antifouling agents in that they could serve as potential effective additives to environmentally friendly commercial antifouling paints due to their non‐toxicity (Tello et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%